Development of starch-clay nanocomposite on recycled paperboard for single use packaging application - Aquinde, Jean Audrey E. (College of Engineering, University of the Philippines Diliman, 2014)
In practice, single-sue packaging such as plastic-coated take-out boxes is not generally regarded as resource materials and is readily discarded for disposal. Thus, a sustainable packaging design is neede since the use of virgin fibers and non biodegradable coating in the packaging material renders it overdesigned for its target useful life.In this study dispersion coating formulations of starch-clay nanocomposite at varying glycerol and montmorillonite (MMT) clay concentrations were developed and applied onto kraft paperboard. The glossy, smooth and transparent characteristics of the coating were found comparable to commercially available plastic films. The tensile strength of the coated board reached thrice of the uncoated board when prepared at 1% and 3% glycerol at low levels of MMT. Scanning electron microscope (SEM)starch (TPS) matrix which suggests the formation of both intercalated and exfoliated structures. Up to 91% drop in oil absorbency and 12% reduction in water vapor permeance were achieved.Atomic force microscope (AFM) height profiles showed significant smoothening of the coating's tecture at geometric average roughness , Rq = 1.384 to 1.575 nm. A shift of the characteristic sharp dip (3630cm-1)in the FTIR spectra attributed to pure MMT to 2358 2360 cm-1in the film indicated a strong interaction between, fully compostable to paper recycling processes.